A study on structural characteristics and metallurgical mechanism of carbides for 440 martensitic stainless steel with different melt refining processes - Yu-An Kuo; Fei-Yi Hung; Jun-Ren Zhao; Bo-Ding Wu; Bo-Chin Huang; Kai-Chieh Chang; Kuan-Jen Chen; Chen-Wang Ku; Chih-Ying Huang; Ho-Yen Hsieh (Journal of Alloys and Metallurgical Systems, 2023)
The melt refining process of Martensitic stainless steel smelting is closely related to the characteristics of the matrix; the formation mechanism and distribution of carbides, especially, influence the mechanical properties of steel. In this study, three different melt refining processes of 440 stainless steel were used for analysis: aluminum reduction process (440 M-Al), silicon reduction process (440 M-Si), and electro slag remelting (440 C-ESR). The results show the main carbides of 440 stainless steel after three different melt refining processes are M7C3 and M23C6. The carbides of 440 M-Al and 440 M-Si are fine particles; the carbide of 440 C-ESR is a small block. The 440 M-Al carbides are micron- and nanoscale-sized particles. The micron-sized carbides solidify and aggregate at the unit cell boundary, and the structure is Cr7C3. There are gaps between the carbide particles, and the solid solution carbon content of the adjacent matrix is high, which makes the hardness of the matrix greater than that of the carbide aggregation area. On the contrary, the matrix of 440 C-ESR solid dissolves many alloying elements, and the fine lump carbide is also Cr7C3. The carbide diffusion interface layer of 440 C-ESR can improve the bonding characteristics of the interface of the carbide and the matrix, thus enhancing the mechanical properties.